Exercise-Induced Improvements in Postprandial Glucose Response Are Blunted by Pre-Exercise Hyperglycemia: A Randomized Crossover Trial in Healthy Individuals - Carter, Steven; Solomon, Thomas P. J. (Frontiers in Endocrinology, 2020)
Background: Exercise improves glycaemic control but the magnitude, and in some cases, the direction of this effect is variable. Ambient hyperglycaemia has been implicated in this exercise response heterogeneity. The current study investigated whether pre-exercise hyperglycaemia directly impacts the effect of exercise on glycaemic control. Methods: Twelve healthy males completed four trials in a randomised, crossover design. Each trial consisted of 24h pre-intervention monitoring, a 7h intervention, and 24h post-intervention monitoring. Glycaemic control was measured throughout the study by continuous glucose monitoring. The four interventions were no exercise (CON) or 45-min of cycling exercise (70%HRmax) preceded by 3.5h of either normoglycaemia (NG-Ex), steady-state hyperglycaemia induced by constant glucose infusion (HG-Ex) or fluctuating glycaemia induced by repeated glucose bolus infusions (FG-Ex). Results: Physical activity and diet were similar between trials, and energy expenditure during exercise was matched between exercise trials (all P>0.05). Mean glucose during the 3.5h±infusion period was higher in HG-Ex (mean±SEM; 7.2±0.4 mmol/L) and FG-Ex (7.3±0.3 mmol/L) compared to CON (4.8±0.2 mmol/L) and NG-Ex (5.0±0.2 mmol/L) trials (P<0.01). Glycaemic variability was greatest in FG-Ex (P<0.01). Following the interventions, the postprandial glucose response (iAUC) was reduced by exercise in NG-Ex compared to CON (321.1±38.6 vs. 445.5±49.7 mmol/L.8h, P<0.05, d=0.81). This benefit was blunted when exercise was preceded by steady-state (HG-Ex, 425.3±45.7 mmol/L.8h) and fluctuating (FG-Ex, 465.5±39.3 mmol/L.8h) hyperglycaemia (both P>0.05 vs. CON). Conclusion: Pre-exercise hyperglycaemia blunted the glucoregulatory benefits of acute exercise upon postprandial glucose response, suggesting that exposure to hyperglycaemia contributes to exercise response heterogeneity. ClinicalTrials.gov identifier: NCT03284216.